The Effect of Digitalization on Firm Performance with the Mediation of Supply Chain Performance and Supply Chain Resilience for the Oil Industry - Muhammad Faris Ghiats (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the influence of digitalization on company performance by considering the mediating role of Supply Chain Performance (SCM) and Supply Chain Resilience (SCR) in the Indonesian fuel industry. Digitalization through the implementation of the Internet of Things (IoT), big data analytics, artificial intelligence (AI), and cloud computing is an important strategy for creating an efficient, responsive, and adaptive supply chain to disruption. The research method uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary data were collected through questionnaires from respondents in fuel companies. The results show that digitalization has a significant positive effect on SCM and SCR, which in turn has a positive impact on firm performance. The influence of digitalization is also proven to indirectly improve performance through the mediation of SCM and SCR. These findings underscore the importance of digital transformation integrated with data-driven supply chain management strategies and operational resilience. This study provides a theoretical contribution by developing a comprehensive and practical conceptual model as a reference for fuel companies in designing effective and sustainable digitalization policies.